FORMULASI MINUMAN SERBUK INSTAN SELEDRI DENGAN PENAMBAHAN VARIASI JENIS JERUK DAN BERAT GULA - May Ayu Pratiwi; Anisya Dwi Anggraini; Faidliyah Nilna Minah; Siswi Astuti (jurnal ATMOSPHERE, 2024)
Celery (Apium graveolens L.) is a plant that has many benefits that can be processed into products in the form of instant powder drinks. Preparation of instant celery powder with the addition of orange juice and sugar. This study aims to determine the effect of the ratio of sugar and the type of orange in the manufacture of instant celery powder. Types of oranges used include mandarin oranges, Siamese, lime, sweet, and lemon. Comparison of the weight of sugar 50, 75, 100, 125, and 150 grams. The quality of instant celery powder was determined by analysis of water content, soluble time, total dissolved solids, solubility, and organoleptic tests. The results showed that A5B4 was the accepted sample, namely the formulation of 500 ml of celery juice, 125 grams of granulated sugar, and 20 ml of lemon juice. Different types of oranges and the ratio of sugar weight affect water content, solubility, dissolution time, organoleptic taste and aftertaste. The acceptance rate of orange celery powder drink to the color organoleptic test was 3.11%, the aroma organoleptic test was 2.96%, the taste organoleptic test was 3.67%, and the aftertaste organoleptic test was 3.30%. The formulation gives a water content value of 7%. The results of the physical test stated that the dissolution time was 96.79 seconds, the total dissolved solids were 15% and the solubility was 88.71%.